2021
DOI: 10.3390/healthcare9020122
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Not Joke about It Too Much! Exposure to COVID-19 Messaging, Attitudes and Protective Behavioral Intentions

Abstract: Our study evaluates the role of exposure to COVID-19 messaging in negativity towards COVID-19 and the intentions to engage in protective behaviors. Building on the theory of planned behavior (TPB), we derive a mediation model and test it in a sample of 737 participants (556 Romanians and 181 Kazakhs). The exposure to general information concerning COVID-19 positively predicts negative attitudes, negative emotions and the emergence of subjective norms in relation to COVID-19, as well as the likelihood of engagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Caserotti et al indicated that as Italy participants' risk perception increased, so did their willingness to accept the vaccine [31]. Furthermore, several social cognitive models have been successfully applied to interpret preparedness behavior in Covid-19, including the protection motivation theory (PMT), the theory of planned behavior (TPB), the health belief model (HBM) [8][9][10]32 To sum up, while the studies mentioned above provide valuable insights, it remains unclear how risk information, especially warning information, interacts with risk perception and whether their interaction has an impact on preparedness behaviors. Little attention has been given to an integrated information-perception-action mediation model to elucidate individual's precautions during Covid-19.…”
Section: Risk Perception and Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Caserotti et al indicated that as Italy participants' risk perception increased, so did their willingness to accept the vaccine [31]. Furthermore, several social cognitive models have been successfully applied to interpret preparedness behavior in Covid-19, including the protection motivation theory (PMT), the theory of planned behavior (TPB), the health belief model (HBM) [8][9][10]32 To sum up, while the studies mentioned above provide valuable insights, it remains unclear how risk information, especially warning information, interacts with risk perception and whether their interaction has an impact on preparedness behaviors. Little attention has been given to an integrated information-perception-action mediation model to elucidate individual's precautions during Covid-19.…”
Section: Risk Perception and Covid-19 Pandemicmentioning
confidence: 99%
“…In the context of epidemics, an abundance of publications have investigated the influencing factors of risk perception and also have assessed the link between risk perception and precautionary behavior [7][8][9][10]. To date, a significant limitation of the existing studies is that they ignore the role of information especially warning that initiates the cognitive processes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it generates an appraisal context in which the pandemic is less likely to be perceived as threatening and therefore stressful. Certainly, such an appraisal tendency may also have negative consequences when it tends to reduce the likelihood of engaging in protective behaviors [ 19 ]. In the context of the COVID-19 pandemic, we would expect that constant rumination about the dangers of the pandemic leads to distress and protective behaviors, while the use of humor in communication about COVID-19 leads to eustress.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Merino et al [ 18 ] used positive and negative affect experienced in relation to COVID-19 quarantine as indicators of eustress and distress, respectively. The COVID-19 pandemic is indeed a global stressor [ 19 , 20 , 21 , 22 ] that can trigger either eustress or distress in the population [ 20 , 23 ]. We have put forward a more comprehensive multidimensional approach of measuring eustress and distress in academic and organizational settings by taking into consideration emotional, physical, and behavioral indicators that discriminate between the two complex psychological states.…”
Section: Introductionmentioning
confidence: 99%
“…TPB has been extensively applied in studies related to various health behaviors, including alcohol consumption [32], tobacco use [33], healthy eating [34], physical exercises [35], health screening [36], and health information sharing [37]. During the COVID-19 pandemic, TPB has been frequently employed to investigate behaviors related to pandemic control [38], vaccination [39], physical exercises [40], healthy eating [41], health protective measures [42], health information-sharing [43], and other behaviors.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%